Psychological characteristics of war veterans after the war in Bosnia and Herzegovina - Zihnet Selimbašić; Azra Kurtić; Mirna Selimbašić; Maja Brkić; Dženita Hrvić (Medicinski glasnik, 2019)
Aim: To determine psychological characteristics of war veterans after the war in Bosnia and Herzegovina (B&H). Methods: The study included 207 war veterans with war experience in B&H. Evaluation of veterans was conducted by the Harvard Trauma Questionnaire (HTQ)-B&H version, Emotion Profile Index (EPI), Life Style Questionnaire (Life Style index-LSI). Results: Veterans who show symptoms of posttraumatic stress disorder (PTSD) had more traumatic experiences and higher level of traumatization than veterans who did not show PTSD symptoms (p=0.000). Low level of reproduction, incorporation, lack of control, self-defence and exploratory and acceptable responses (p=0.000), lack of control (p=0.025) and deprivation (p=0.013) were shown on the emotional profile by war veterans suffering from post-traumatic stress disorder. Negation, intellectualization and compensation were coping strategies for traumatic experiences and symptoms of PTSD, used by war veterans. Conclusion: War veterans with post-traumatic stress disorder experienced more traumatic experiences and show more severe symptoms of post-traumatic stress disorder. In the emotional profile, there was a lower level of emotional states, and coping strategies with posttraumatic stress disorder were negating, intellectualization and compensation. The treatment of post-traumatic stress disorder is becoming a conspicuous public health problem.
Keywords: aftermath; mental health; war traumatization